1990
DOI: 10.1111/j.1745-4549.1990.tb00830.x
|View full text |Cite
|
Sign up to set email alerts
|

METHYL BROMIDE, TIME and TEMPERATURE of EXPOSURE ON APPLE QUALITY

Abstract: ABSTRACT. The use of methyl bromide (MeBr) as a fumigant to control codling moth in ‘Delicious’apples resulted in a loss of firmness, internal color and therefore a reduction in the amount of acceptable fruit. Time and temperature of MeBr exposure were directly related to firmness and internal color loss. As the exposure time was increased beyond 2 h and exposure temperature above 6°C firmness and internal color loss were accelerated. an 8‐day ambient storage period exacerbated firmness and internal color los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The share of Fuji apples expected to meet Japanese consumer standards, h, is based on industry estimates that ranged from 10-20% to 24% (Smith; Archer, 2004). High-quality Fuji apples are relatively tolerant of methyl bromide fumigation compared to Red Delicious varieties (Drake, Moffitt, and Mattheis;and Archer, 2006). Research on Red Delicious found that after fumigation and storage only 83.8% of fumigated apples were marketable compared to 100% of nonfumigated apples.…”
Section: Phytosanitary Protocol Program Parametersmentioning
confidence: 99%
“…The share of Fuji apples expected to meet Japanese consumer standards, h, is based on industry estimates that ranged from 10-20% to 24% (Smith; Archer, 2004). High-quality Fuji apples are relatively tolerant of methyl bromide fumigation compared to Red Delicious varieties (Drake, Moffitt, and Mattheis;and Archer, 2006). Research on Red Delicious found that after fumigation and storage only 83.8% of fumigated apples were marketable compared to 100% of nonfumigated apples.…”
Section: Phytosanitary Protocol Program Parametersmentioning
confidence: 99%